Evaluating the construct validity and test-retest reliability of the Orthotic Patient-Reported Outcomes–Mobility (OPRO-M) short forms in lower limb orthosis users - Geoffrey S. Balkman; Phillip M. Stevens; Eric L. Weber; Alyssa M. Bamer; Rana Salem; Bretta L. Fylstra; Sara J. Morgan; Brian J. Hafner (PLoS ONE, 2025)
Lower limb orthoses (LLOs) are often prescribed to facilitate mobility in individuals with functional impairments. The Orthotic Patient-Reported Outcomes – Mobility (OPRO-M) is a self-report instrument developed recently to measure LLO users’ perceived mobility with an orthosis. An observational, prospective, psychometric validation study was conducted to evaluate the construct validity and test-retest reliability of the OPRO-M 12- and 20-item short forms. LLO users were recruited from orthotic clinics across the United States. Participants were administered four self-report instruments (OPRO-M, Orthotic and Prosthetic Users Survey – Lower Extremity Functional Status, Lower Extremity Functional Scale, and Patient-Reported Outcomes Measurement Information System – Physical Function) and three performance-based instruments (10-meter Walk Test, Timed Up and Go Test, and Two-Minute Walk Test) during an in-person assessment. Self-report instruments were re-administered via an online survey sent to participants 7 days later. Convergent validity was assessed by comparing OPRO-M scores to those from co-administered self-report and performance-based instruments. Known groups validity was evaluated by comparing scores from patients grouped by clinician-assigned mobility level. Test-retest reliability was assessed by comparing scores from the in-person and follow-up assessments. Standard error of measurement (SEM) and smallest detectable change (SDC) were derived from test-retest reliability coefficients. A total of 104 LLO users (51% male, mean age = 53 years) completed both assessments. OPRO-M short form scores correlated strongly with those from self-report (ρ = 0.84–0.91) and performance-based (|ρ| = 0.73–0.83) instruments. OPRO-M short form scores also effectively differentiated all mobility groups except household and limited community ambulators. The OPRO-M short forms showed excellent test-retest reliability (ICC = 0.93–0.94) and low measurement error (SEM = 2.4–2.6, SDC = 5.5–6.0). These results provide sound evidence of the OPRO-M short forms’ validity and reliability when used to measure mobility in LLO users. These instruments are promising, population-specific alternatives to generic surveys with psychometric performance comparable to or better than established self-report instruments.